AN ENHANCE SYSTEM SMART TOILET BASED ON RECYCLE GREEN CONTROL - Solly Aryza; Siswa Pratama; Muhammad Ikbal (Sean Institute, 2022)
Klambir 5 village is an underdeveloped area in North Sumatra in the current era of technology, technology is developing rapidly in the current era, along with the development of technology, there are impacts. Control of electronic equipment can be done with smart bathroom applications (smart badroom) controlling electronic equipment for water treatment is a very important requirement in the life of all living things, especially humans. In primary needs, water is used for drinking, washing, bathing and so on. In addition, water can also be used as a hydroelectric power plant, rice field irrigation system, transportation and others. The purpose of this study is to design a device that can control the output of water in the ablution tap and control the filling of the water reservoir. In designing this tool using Arduino Mega 2560 as data processor and keypad as well as water float sensor and Infrared Proximity Sensor as input and DC pump, relay and solenoid valve as output. With the design of this tool, it can fill the water reservoir automatically and can control the output of water in the ablution water faucet